A Case of Penetrating Foreign Body Causing Mild Symptoms of Acute Carpal Tunnel Syndrome. (6th August 2020) - AlHasan, Rashed N.; Louri, Nayef A.
Carpal tunnel syndrome (CTS) is a neuropathy brought about by the entrapment and compression of the median nerve as it travels through the carpal tunnel. The hallmark of classic CTS is pain or paraesthesia (numbness, burning, or tingling) in the palmar aspect of the first 3 digits, as well as the radial aspect of the fourth digit. Although idiopathic in nature, many risk factors have been attributed to the development of CTS. These factors include diabetes mellitus, acromegaly, thyroid disease, rheumatoid arthritis, pregnancy, the use of steroids, and the repetitive use of hand and wrist. The prevalence also seems to be higher in obese women. In literature, trauma, foreign body, tumors, or anatomical variations are considered to be infrequent causes of CTS. A rare form of CTS is the acute carpal tunnel syndrome (ACTS) that presents mainly after injuries to the upper extremities. The patient typically acknowledges trauma to the wrist secondary to a foreign body at the time of injury. In some cases, small fragments may penetrate the wrist and remain unnoticed causing acute neurological symptoms. In literature, there were limited studies that reported the development of ACTS secondary to missed foreign bodies following trauma. This report presents a case of ACTS sustained following a penetrating foreign body (pellet) to the right wrist. Removal of the foreign body resulted in complete recovery with no neurological sequelae.